KONSERVASI EX SITU CENDANA (Santalum album L.): APLIKASI DAN TANTANGANNYA - Soekotjo Soekotjo (Research Center for Biology-Indonesian Institute of Sciences, 2001)
Managing genetic resources of cendana/sandalwood (Santalum album L)requires an understanding of the biological dynamics of its population in which they exist. There are two strategies of conservation i.e. maintaining existing protected areas (in situ) and ex situ collections of various types.Ex situ methods include gene banks: clonal bank and breeding population. The two methods (in situ and ex situ) are complementary. Preservation of genetic resources in gene bank is essential for users of germplasm who need ready access.Ex situ conservation plantations are expensive to establish and maintain, and their use will thus be generally confined to species/ provenances of proven socio-economic value. This paper discussing collection of genetic resources of several population and establishment/ management of ex-situ conservation plantations.